(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information about the methods and ways of creating hydronymic terms. At the same time, many artificial terms are created on the basis of simple terms in economic terminology, and it is supported by examples.